Gallbladder perforation following transarterial chemoembolisation; a rare but serious complication. Issue 2 (21st February 2013) - Lim, Eu Jin; Spanger, Manfred; Lubel, John S
Abstract : Transarterial chemoembolisation (TACE) is the mainstay of treatment for large or multifocal hepatocellular carcinoma (HCC). However, this procedure is not without potential complications. We report the case of a 72-year-old man with cirrhosis with HCC treated by TACE using drug-eluting beads. He developed persistent fever and severe right upper quadrant pain post-procedure. CT abdomen revealed a large fluid collection closely abutting the gallbladder and tracking inferiorly along the right flank. This fluid collection originated from the gallbladder and contained locules of gas with a contrast-enhancing wall, consistent with an infected biloma. These imaging findings confirmed gallbladder perforation complicating TACE. The development of gallbladder perforation post-TACE from acute ischaemic cholecystitis producing gallbladder wall necrosis is exceedingly rare. The presence of gallbladder perforation must be recognised in patients with persisting symptoms and imaging evidence of a perihepatic fluid collection because specific treatment with intravenous antibiotics and percutaneous drainage of the biloma is necessary.